2018
DOI: 10.1097/md.0000000000010936
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective observational study of breast reconstruction with extended latissimus dorsi flap following skin-sparing mastectomy

Abstract: The study was aimed to evaluate oncological safety and patient satisfaction in relatively late stage breast cancer patients who was treated with skin-sparing mastectomy (SSM) followed by breast reconstruction with an extended latissimus dorsi (LD) flap. Oncological safety, postoperative complications, and cosmetic results were retrospectively analyzed in patients who underwent extended LD flap breast reconstruction following SSM between October 2011 and August 2014. A total of 62 patients who underwent 63 brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The traditional open technique has been described previously ( 24 ). It leaves a notable scar on the breast and back.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional open technique has been described previously ( 24 ). It leaves a notable scar on the breast and back.…”
Section: Methodsmentioning
confidence: 99%
“…The overall number of skin necrosis is in concordance with the previous literature showing a necrosis rate of 0%-17%. [34][35][36][37][38] The dilemma is associated with the surgical technique of SSM, the thickness of skin flaps, and the amount of a residual breast tissue left especially on the anterior margin. Contradictory to each other, it has been shown that the skin flap thickness more than 5 mm increases the amount of residual breast tissue 39 and the flap thickness less than 5 mm increases the risk of skin necrosis.…”
Section: Ptmentioning
confidence: 99%
“…In patients who have undergone breast reconstruction using an extended latissimus dorsi muscle flap decreased latissimus dorsi muscle mass after radiation therapy is frequently observed due to factors including muscle atrophy and fibrosis [9,10]. However, in BCS, as muscle tissue is not used for breast reconstruction, it is predicted that the amount of volume decrease would be relatively small.…”
Section: A B Cmentioning
confidence: 99%